2008
DOI: 10.1016/j.cattod.2007.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic performance and QXAFS analysis of Ni catalysts modified with Pd for oxidative steam reforming of methane

Abstract: Pd-Ni bimetallic catalysts prepared by co-impregnation and sequential impregnation methods were compared in the catalytic performance in oxidative steam reforming of methane. The sequential impregnation was more effective to the suppression of hot spot formation. According to the structural analysis by in-situ quick-scanning X-ray absorption fine structure (QXAFS) during the temperature programmed reduction, the sequential impregnation method gave the bimetallic particles with higher Pd surface composition bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…Furthermore, as showed in Figures 1c and 1d, the bimetallic catalysts with 0.5 and 1.0 Ni wt % have peaks at 598 and 621 K, respectively, due to the reduction of NiO species to Niº. [38][39][40] The position of these peaks is slightly modified as the Ni loading is increased. A similar behavior was observed by other authors when studying Ni monometallic catalysts.…”
Section: Resultsmentioning
confidence: 83%
“…Furthermore, as showed in Figures 1c and 1d, the bimetallic catalysts with 0.5 and 1.0 Ni wt % have peaks at 598 and 621 K, respectively, due to the reduction of NiO species to Niº. [38][39][40] The position of these peaks is slightly modified as the Ni loading is increased. A similar behavior was observed by other authors when studying Ni monometallic catalysts.…”
Section: Resultsmentioning
confidence: 83%
“…31,32 Similar catalytic systems (Pt-Ni, Pd-Ni, Rh-Ni) give high methane conversion in the oxidative steam reforming of CH 4 . [33][34][35] Rh containing bimetallic catalysts show high efficiencies in dry 36 and steam 35 reforming of methane. Recently, it was demonstrated that the catalytic performance of CeO 2 depends on the particle size, due to the difference of the reducibility and therefore the number of acidic sites.…”
Section: +mentioning
confidence: 99%
“…For example, while CO adsorbs non-dissociatively on Rh nanoparticles on fully oxidized ceria films, it dissociates on partially reduced films. 34 Similarly, NO dissociation is enhanced when Rh particles are supported on reduced CeO 2 (111). 38 Several hypotheses have been put forward, including electron transfer from ceria to Rh particles, structural variation in the Rh particles, or O spillover from Rh to ceria.…”
Section: +mentioning
confidence: 99%
“…Here, one strategy is the combination of high reducibility of noble metals with high reforming activity of Ni. The Pt-Ni and Pd-Ni bimetallic catalysts supported on γ-Al 2 O 3 were investigated and the relation between the structure of bimetallic particles and the resistance to hot-spot formation in oxidative reforming of methane has been reported [7][8][9][10][11][12]. Here, we tested the bimetallic catalysts supported on α-Al 2 O 3 with larger Ni loading amount, which will be more applicable to a practical process.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the high cost and limited availability of noble metals, the main component should be nickel. Therefore, our group has been developing Ni-based catalysts modified with a small amount of noble metal for oxidative reforming of methane with high resistance to hot-spot formation [7][8][9][10][11][12]. Here, one strategy is the combination of high reducibility of noble metals with high reforming activity of Ni.…”
Section: Introductionmentioning
confidence: 99%